Finding Meaning Behind Accidents through Self-Guidance: A Phenomenological Study on Trauma Experience and Recovery - Umi Umayah; Dina Astriyani; Rasikah Anis Mardatilah; Riska Yulandari; Asti Haryati; Cindy Ainun Nabilla; Yopi Azhari Jayadi (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Trauma resulting from traffic accidents often leads to significant psychological impacts, such as excessive fear, insecurity, nightmares, and avoidance behaviors towards situations that remind the victim of the incident. Purpose: This study aims to explore the profound experiences of victims of single-vehicle accidents in understanding the trauma they have experienced and the psychological recovery process they undergo. Method: This research employs a qualitative phenomenological approach, collecting data through in-depth interviews, observations, and documentation, which are then analyzed using phenomenological stages. Results: Participants went through complex emotional phases, starting with shock and extreme fear, which then developed into anxiety and avoidance of situations related to the accident. Their psychological recovery process was gradual, involving family support, self-reflection, acceptance, and the search for deeper meaning in life. Conclusion: The search for meaning and social support plays a crucial role in the psychological recovery of accident victims, showing that post-traumatic growth can occur. Contribution: This study serves as a foundation for developing more empathetic trauma counseling practices, based on validating experiences and reconstructing meaning to aid victims in their recovery.